Designation of a replacement name for Capnioneura veronicae nomen nudum (Capniidae Plecoptera) - Vinçon, Gilles (Illiesia, 2011)
Capnioneura veronicae nomen nudum is replaced by C. gouanerae. The types of C.gouanerae are designated.
Keywords: Capniidae; entomology; Plecoptera; Capnioneura; Capnioneura veronicae; Turkey; C. gouanerae; name replacement; entomologija; vrbnice; Turčija